Combined experimental drought and nitrogen loading: the role of species‐dependent leaf level control of carbon and water exchange in a temperate grassland. (26th January 2021) - Kübert, A.; Kuester, E.; Götz, M.; Dubbert, D.; Eiblmeier, M.; Werner, C.; Rothfuss, Y.; Dubbert, M.
Abstract: Nitrogen (N) loading and extreme drought strongly alter biomass production, species composition and carbon and water fluxes of temperate grasslands. Such changes at the community level are often attributed to species‐ and functional group‐specific responses in phenology and/or physiology. In a multifactorial field experiment, we studied the responses of three abundant grassland species (forb Centaurea jacea, grasses Arrhenatherum elatius and Dactylis glomerata ) to N loading and extreme drought, focusing on responses of carbon and water relations at the leaf level. We analysed (1) changes in bulk leaf N (uptake efficiency of additional N), (2) adaptation of plant water status (leaf water potential) and (3) impact on leaf carbon and water fluxes. We observed more efficient N utilization in the two grasses compared to C . jacea . Naturally occurring summer drought significantly impacted the plant water status of all species, while extreme drought treatment only further affected water status during and after summer drought. C . jacea was able to maintain much lower leaf water potentials compared to the grasses during drought. Despite these clear species‐specific responses to N loading and drought, the species were able to maintain homeostasis of leaf carbon and water fluxes. Thus, strong declines in the (community) carbon sequestration observed at this site during the (natural) summer drought were not related to leaf physiological responses in assimilation, but were driven by phenological adaptions of the species community: the drought‐sensitive grasses, even though exhibiting higher N uptake efficiency, responded with a shortened life cycle to severe summer drought. Abstract : Abundant grassland species maintained leaf level carbon and water fluxes under strongly altered water and nitrogen availability (treatments).